More electric aircraft conversion to all-electric during ground operations: battery powered landing gear drive system - Deja, Jakub; Dayyani, Iman; Nair, Varun; Skote, Martin (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Raising awareness about environmental issues moves the aerospace industry towards electrification and the corresponding solutions are already present at some airports. However, commercial aircraft are the missing links in claiming the all-electric ground operations. They rely on fossil fuels without any electric alternative due to the technological inability to store large amounts of energy while maintaining low weight of batteries. The issue diminishes if an electric system uses only a fraction of energy normally consumed by the engines and comprises kinetic energy recovery. Accordingly, this paper demonstrates the landing gear drive system for a narrowbody air-plane which has the sustainable and economic means to replace all onboard engines throughout ground operations. The system is simulated in MATLAB/Simulink and leads to the kinematic results which are based on the real drive cycles. The kinematics are subsequently used to estimate the overall on-ground power and energy demand of a more electric aircraft (MEA). The impact is maximized with the components scaled according to performance metrics and two-speed gear ratio optimization. The net fuel advantage is demonstrated for different ground operation modes, taxi times and flight path lengths.